Managing the refugee crises in South Asia: The role of SAARC. (June 2019) - Ahmed, Zahid Shahab
South Asia is home to roughly three million refugees and their long-term presence brings enormous challenges. South Asia's history of colonialism, low economic development, and intra- and inter-state conflicts have contributed to the large-scale refugee movement and the lack of capacity to address the problem. This article examines the history, current activity and potential for regional cooperation in South Asia to address the issue. The article focuses particularly on the South Asian Association for Regional Cooperation, the structure and culture of the organization and the likelihood of it addressing the politically complex issue of forced migration.